The Effect of Physical Exercise on College Students' Mental Health and General Self-efficacy - Yinghua Zhao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Objective: The objective of this study is to examine the relationship between physical exercise, mental health and general self-efficiency among college students Method: The random sampling method is used to select undergraduates from colleges, wherein the study uses the physical exercise rating scale (PARS- -3), the General Self-Efficacy Scale (GSES) and the Symptom Self-Rating Scale (SCL-90) to survey 366 college students, and use descriptive statistics, t-test, analysis of variance to analyze resulting data. Results: The amount of physical exercise reported by men is higher than that of women (t=3.95), the amount of physical exercise of urban students is higher than that of rural students (t=2.96); The self-efficacy and mental health of the large exercise group are higher than those of the small exercise group (t = 7.88, 8.26). There is a significant positive correlation between the amount of physical exercise and the level of self-efficacy and mental health (r=0.42, 0.32, 0.36); Self-efficacy plays a partially mediating role vis-a-vis the influence of physical exercise on mental health. Conclusion: Physical exercise can directly affect the level of mental health, and it can also indirectly affect the level of mental health through self-efficacy. The correlation coefficients of physical exercise amount, body self-esteem and self-efficacy were significantly correlated at 0. 001 level. Body self-esteem and physical exercise had positive predictive effects on self-efficacy